PERLINDUNGAN HUKUM BAGI JABATAN NOTARIS BERDASARKAN PASAL 66 UUJN SETELAH LAHIRNYA PUTUSAN MAHKAMAH KONSTITUSI REPUBLIK INDONESIA NOMOR: 49/PUU-X/2012 - Mulya ML, Putu Wisnu Pradnyan; Wairocana, I Gusti Ngurah; Putra Santika, Ida Bagus Agung (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 1 No 2 (2016), 2016)
Notary Supervisory Regional Assembly ( MPD) is an institution that is based upon the provisions of Article 66 and Article70 (a) of Law No. 30 of 2004 Regarding Notary. The presence of MPD in the practice of providing protection for the notary public to call as a witness to the deed is made?? for the purpose of investigations or proceedings in a civil or criminal case. Based MKRI’s Decision Number 49/PUU-X-2012 dated May 28, 2013, authorized the MPD as a protective institution notary office to be reduced, so that each call-related notary deed made?? in the examination as a witness or as a defendant/suspect by police, prosecutors and following a court decision photo copy minute deed or notarial protocol in storage no longer require the approval ofthe MPD. Issues arising under the MKRI’s decision are the lack of legal protection forthe notary, but notary publicis an officer who makes authentic act that has legal force and position it perfectly guaranteed by law. Based on the problems, can be formulated in concerns about how the form of legal protection for the office of notary public in the event ofa notary as a witness by calling the police or the courts after the birth of the MKRI Judgment and Decision MKRI whether it also resulted in  the provision of Article 70 (a) does not need to be implemented by the MPD in relation to the result of calling the notary deed is made.
Keywords: Legal Protection, Incumbency, Notary, Decision, the Constitutional Court, MPD